2008
DOI: 10.1111/j.1469-8986.2008.00650.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological correlates of direct selection by color

Abstract: We report an experiment using event-related potentials (ERPs) to study selection by color uncontaminated from selection by location. Participants monitored an RSVP sequence for a given target letter that could appear in upper- or lowercase. Prior to the sequence, a cue indicated the most likely color of the target letter. Replicating E. Vierck and J. Miller (2005), upper-/lowercase discrimination accuracy was higher following valid than invalid color cues. Within the ERPs, the target onset produced a negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 41 publications
9
11
0
Order By: Relevance
“…This had an influence in behavioral measures obtained in an orthogonal task, as RT to valid (attended) trials were faster than to invalid (unattended) trials. These behavioral results are in line with previous findings on attention to simple attributes (Griffin et al 2001;Krauzlis and Adler 2001;Vierck and Miller 2008;Vossel et al 2009), categories (Aranda et al 2010a;Esterman and Yantis 2010;Puri et al 2009), and idiosyncratic expectations about well-known stimuli (Aranda et al 2010b;faces vs. houses, Faulkner et al 2002;Puri and Wojciulik 2008). Cue validity had an equivalent effect on the responses to the famous and unfamiliar faces, which might have been taken as evidence that the effect was comparable for the famous and unfamiliar items.…”
Section: Discussionsupporting
confidence: 91%
“…This had an influence in behavioral measures obtained in an orthogonal task, as RT to valid (attended) trials were faster than to invalid (unattended) trials. These behavioral results are in line with previous findings on attention to simple attributes (Griffin et al 2001;Krauzlis and Adler 2001;Vierck and Miller 2008;Vossel et al 2009), categories (Aranda et al 2010a;Esterman and Yantis 2010;Puri et al 2009), and idiosyncratic expectations about well-known stimuli (Aranda et al 2010b;faces vs. houses, Faulkner et al 2002;Puri and Wojciulik 2008). Cue validity had an equivalent effect on the responses to the famous and unfamiliar faces, which might have been taken as evidence that the effect was comparable for the famous and unfamiliar items.…”
Section: Discussionsupporting
confidence: 91%
“…The preparatory state triggered by the symbolic cue can be referred to various dimensions of the upcoming stimulus, such as its spatial location, temporal occurrence, color, direction of motion, or even the semantic meaning of linguistic stimuli. This preparatory state or expectation is known to optimize the subsequent processing of the target (e.g., Correa, Lupiáñez, Madrid, & Tudela, 2006;Griffin, Miniussi, & Nobre, 2001;Krauzlis & Adler, 2001;Ruz & Nobre, 2008;Vierck & Miller, 2008;Vossel, Weidner, Thiel, & Fink, 2009), probably by providing a competitive bias that favors task-relevant representations over competing representations (Bar, 2003;Stokes, Thompson, Nobre, & Duncan, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Previous research has shown that devoting attention to general stimulus attributes can optimize target processing regardless of stimulus type (Aranda et al, 2010;Esterman & Yantis, 2010;Griffin et al, 2001;Krauzlis & Adler, 2001;Puri et al, 2009;Ruz & Nobre, 2008;Vierck & Miller, 2008;Vossel et al, 2009). This could have led one to expect validity effects for nonself stimuli in the present paradigm.…”
Section: Familiar Facementioning
confidence: 99%
“…The color cue in the invalid condition should lead to the selection of the distractor letter in the cued color, if participants used the color cue to help them find the target. Thus, we expected to see ERPs in the invalid cue condition that were initially similar to those observed for target processing by Vierck and Miller (2008). But processing of the distractor letter should terminate as soon as the letter is identified as a distractor.…”
Section: Methodsmentioning
confidence: 87%
“…Color as used in this experiment was only additional information; it was not strictly needed to fulfill the task requirements because only one target letter appeared in each RSVP sequence. Vierck and Miller (2008) reported effects of validity at occipital recording sites in the form of a broad slow negativity (BSN) and a positivity around 240 ms at parietal and central recording sites, so the current studies will focus only on these ERPs. Although P300 modulation was also expected, we limited the analysis to earlier potentials because these are of main interest.…”
Section: Methodsmentioning
confidence: 99%